Managing institutional complexity through strategic agility: The internationalization journey of a Moroccan MNC - Amaral-Baptista, M.; Rottig, D. (AIB Insights, 2026)
This study explores how emerging market multinational corporations (EMNCs) leverage strategic agility, developed at home, to manage institutional complexity when expanding abroad. We analyze the two-and-a-half-decade internationalization journey of Intelcia, a Moroccan global business process outsourcing provider, by examining core agility drivers: strategic sensitivity, leadership unity, and resource fluidity. Our key insight is that home-grown strategic agility enhances EMNCs’ ability to manage institutional complexity and market uncertainties during international expansion, thereby creating a competitive advantage. We forward a prescriptive framework detailing four strategic agility phases for managing institutional complexity, valuable for both EMNC leaders and international business educators.